Electrophysiological correlates of suicidality - Rakús, Tomáš; Hubčíková, Katarína; Bruncvik, Lucia; Pechanová, Zuzana; Brunovský, Martin (Psychiatria Danubina, 2021)
Suicidal risk assessment is still a major challenge not only in psychiatric practice. Clinical investigation of suicidality can be significantly improved by using standardized scales for assessing suicide risk. The choice of a method for assessing suicidality also has significant implications for the search of valid available biomarker of suicidal behavior, where a less complex suicidality assessment procedure yields inaccurate results. This article offers an overview and analyzes in detail clinical studies of suicidality by electrophysiological methods since 2005 to 5/2020, especially in connection with presumed pathophysiological mechanism of the "suicidal brain" and the chosen method of sucidality assessment. Electrophysiological methods such as quantitative electroencephalography indicators, event-related potential, loudness dependence of the auditory evoked potential, polysomnography and heart rate variability offer a robust battery of easily available methods for assessing impaired emotional regulation. Nowadays it is unfortunately very difficult to point out the optimal electrophysiological examination of suicidal behaviour because of conflicting conclusion of presented studies which have been probably caused by various suicidal risk assessments, not always available data on affecting medication prior to testing and small samples of suicidal participants among studies. The most consistent and hopeful results are presented by evaluation of theta power by quantitative electroencephalography, although there are also few conflicting conclusions. The authors of this paper believe that this article could be good starting point for further research of electrophysiological methods in the field of suicidality.
Keywords: prevence sebevražd; rizikové faktory; pokus o sebevraždu; Humans; lidé; Suicide Prevention; Suicide, Attempted; sebevražedné myšlenky; Risk Factors; Suicidal Ideation